Tribal Justice, Tribal Court: Strengthening Tribal Justice Systems Using Restorative Approaches, South Dakota, 2022 - Riley, Lorinda ([Verlag nicht ermittelbar], 2024)
The purpose of this project was to develop a culturally relevant crime seriousness index specific to the Sisseton-Wahpeton Oyate (SWO) tribe while working closely with community partners. Informal background interviews with key stakeholders provided a foundation on traditional crime management by the community. These interviews informed the creation of an SWO-specific adaptation of the Sellin-Wolfgang crime seriousness index following an online survey conducted in 2022 with SWO community members (n=44 completed surveys). Aggregated survey data have been released as a zipped package as it was received by ICPSR. Please refer to the study documentation for details on the index items and instructions on how to obtain the raw research data. The Final Report released by NIJ contains the full SRO crime seriousness index as Appendix D.